2017
DOI: 10.1177/1091142117715112
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Financial Implications of Public Quality Disclosure? Evidence from New York City’s Restaurant Food Safety Grading Policy

Abstract: Grading schemes are an increasingly common method of quality disclosure for public services. Restaurant grading makes information about food safety practices more readily available and may reduce the prevalence of foodborne illnesses. However, it may also have meaningful financial repercussions. Using fine-grained administrative data that tracks food safety compliance and sales activity for the universe of graded restaurants in New York City and its bordering counties, we assess the aggregate financial effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…At first glance, this suggests that the rise in mean sales taxes offsets declines in mean fine revenue. However, Meltzer et al () found little effect on overall restaurant sales, so caution is required here; if impacts of grades are zero‐sum then public grading may lead to a net decrease in total public revenues. Future work should focus on the long‐term effects of public restaurant grading in order to assess implications for total public revenues once high rates of compliance (A grades) are sustained for multiple years.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…At first glance, this suggests that the rise in mean sales taxes offsets declines in mean fine revenue. However, Meltzer et al () found little effect on overall restaurant sales, so caution is required here; if impacts of grades are zero‐sum then public grading may lead to a net decrease in total public revenues. Future work should focus on the long‐term effects of public restaurant grading in order to assess implications for total public revenues once high rates of compliance (A grades) are sustained for multiple years.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, in a time of increasing competition for public resources, understanding the potential effects of these public health initiatives on municipal government revenues is critical and yet largely unexplored. Previous work by Meltzer et al () found little evidence of impacts (positive or negative) from the New York City grading policy on restaurant and bar sales. While sales increased, so did sales in similar establishments just outside the city.…”
Section: Literature Review On Public Gradingmentioning
confidence: 87%
See 3 more Smart Citations